Sensory Characreristics of Tamarillo Syrup - Nadia Hendria Putri; Rahmi Holinesi; Kasmita Kasmita; Sari Mustika (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study was conducted to analyze the effect of different sugar concentrations on the sensory characteristics of tamarillo (Solanum betaceum) syrup. Tamarillo naturally has a strong sour taste and a short shelf life. Processing tamarillo into syrup is an innovative solution to balance its flavor, extend its shelf life, and increase the market value of this less-preferred fruit. The research was carried out in May 2025 at the Culinary Workshop, Faculty of Tourism and Hospitality, Universitas Negeri Padang. This study employed a true experimental method using a Completely Randomized Design (CRD), consisting of three sugar concentration treatments: 125 grams (X0), 100 grams (X1), and 150 grams (X2), each replicated three times. A sensory evaluation was conducted to assess the quality of the tamarillo syrup. The sensory assessment focused on four parameters: color, aroma, texture, and taste. The evaluation was performed by 30 untrained panelists, all of whom were culinary students at Universitas Negeri Padang. The data obtained were analyzed using ANOVA, followed by Duncan’s Multiple Range Test if significant differences were found. The results showed that sugar concentration had a significant effect on taste, but no significant influence on color, aroma, or texture. The 150-gram sugar treatment (X2) produced the highest overall scores, with deep red color (2.14), fresh tamarillo aroma with cinnamon notes (2.21), and a balanced sweet-sour taste (2.79). It can be concluded that the 150-gram sugar treatment (X2) resulted in the best sensory quality.